2013
DOI: 10.1080/21632324.2013.800701
|View full text |Cite
|
Sign up to set email alerts
|

Cultural transmission and contraceptive use: evidence from USA-Mexico migration

Abstract: We estimate the impacts of international migration on modern contraceptive use of women in Mexico. We find that women belonging to migrant families or who had past migration experience had a higher propensity to use modern contraceptives. We obtain these effects after controlling for traditional economic variables such as income and access. To establish a causal effect, we use historic municipality level return migration as instruments for the current decision to migrate. We argue that these results are robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The impact of migration on the knowledge of at least one contraceptive method is very large, corresponding to a 37.4 % increase. This result is in line with that found by De (2013): in Mexico, women from migrant families are 75 % more likely to use birth control pills and 36 % more likely to use condoms than their non-migrant counterparts. In the sample of all women, the statistically significant impacts are obtained among migrant households living in rural areas: women have a higher knowledge of contraceptive methods and their children are more likely delivered in safer conditions.…”
Section: Occurrence Of Pregnancy and Child Health Caresupporting
confidence: 81%
See 1 more Smart Citation
“…The impact of migration on the knowledge of at least one contraceptive method is very large, corresponding to a 37.4 % increase. This result is in line with that found by De (2013): in Mexico, women from migrant families are 75 % more likely to use birth control pills and 36 % more likely to use condoms than their non-migrant counterparts. In the sample of all women, the statistically significant impacts are obtained among migrant households living in rural areas: women have a higher knowledge of contraceptive methods and their children are more likely delivered in safer conditions.…”
Section: Occurrence Of Pregnancy and Child Health Caresupporting
confidence: 81%
“…Analogously, in their study on rural Guatemala, Lindstrom and Munoz-Franco (2005) found that contraceptive use increases and fertility falls with variables such as having family members in urban or international destinations and living in a community where urban migration is common. De (2013) showed that women in Mexico belonging to migrant families have a higher propensity to use modern contraceptives. Kanaiaupuni and Donato (1999), Frank and Hummer (2002), Hildebrandt and McKenzie (2005) used the same Mexican data to investigate the effects of migration on infant mortality and birth weight, finding positive effects for children living in households with at least one migrant.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-three of the papers were published in a peer-reviewed journal, two were PhD dissertations [ 5 , 30 ], and one was an international report [ 45 ]. The top three health topics that were studied were related to health-seeking strategies ( n = 9) [ 18 , 19 , 23 26 , 29 , 31 , 32 ], issues related to sexual and reproductive health ( n = 9) [ 36 , 41 , 42 , 44 46 , 48 50 ], and healthcare support ( n = 7) [ 18 , 22 , 27 , 28 , 34 , 35 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Articles researching those who remain behind were mainly based in the global South, focusing on North and Central America ( n = 6) [ 41 , 43 , 44 , 47 49 ], Africa ( n = 5) [ 5 , 36 , 37 , 39 , 45 ], Asia ( n = 4) [ 35 , 38 , 40 , 50 ], and the Caribbean ( n = 1) [ 8 ]. Furthermore, two of the included articles [ 42 , 46 ] analysed multiple countries when studying transnational social exchanges and their influences on those who remain behind.…”
Section: Resultsmentioning
confidence: 99%
“…Mobility has been associated with major benefits for the individuals who move, the settings they enter and the communities they leave (Black & Castaldo, 2009;Sutherland, 2013). Specific forms of benefit may be economic (De & Ratha, 2012;de Haas, 2006;Lokshin, Bontch-Osmolovski, & Glinskaya, 2010;Sikder & Ballis, 2013), social (De, 2013;de Haan, 1999;de Haas, 2007;Hampshire, 2006;Lind & Agergaard, 2010;Nakamuro, 2010) and individual (de Haan, Kirsten & Rwelamira, 2003;Sikder & Ballis, 2013) in nature. Sad to say, recognition of the positive aspects of mobility is rarely present in the HIV literature, which more often than not focuses on difficulties, problems and risks as we will see below.…”
Section: Men Mobility Money and Riskmentioning
confidence: 97%